2006
DOI: 10.1001/archotol.132.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Montelukast and Pseudoephedrine in the Treatment of Allergic Rhinitis

Abstract: To compare montelukast sodium and pseudoephedrine hydrochloride in the treatment of seasonal allergic rhinitis. Design: A 2-week, parallel, randomized, double-blind study with rolling enrollment. Setting: Tertiary care medical center. Patients: A total of 58 adult subjects with ragweed allergic rhinitis as documented by positive findings on a skin test to ragweed and history of symptoms during previous seasons. Interventions: After recording their own baseline nasal symptoms, nasal peak inspiratory flow (NPIF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 24 publications
0
26
0
6
Order By: Relevance
“…In the literature, authors usually adopt a cutting point of 120 l/min for symptomatic individuals, and sensitivity and specificity higher than 75% 7 . Mucha et al 12 have already used the NIPF as an instrument in the assessment and treatment of individuals with allergic rhinitis, thus showing its usefulness in patients with this disease. Bhatia et al 15 also utilized the NIPF as the only assessment method for nasal patency improvement in seasonal rhinitis, comparing the treatment between desloratadine and intranasal budesonide.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, authors usually adopt a cutting point of 120 l/min for symptomatic individuals, and sensitivity and specificity higher than 75% 7 . Mucha et al 12 have already used the NIPF as an instrument in the assessment and treatment of individuals with allergic rhinitis, thus showing its usefulness in patients with this disease. Bhatia et al 15 also utilized the NIPF as the only assessment method for nasal patency improvement in seasonal rhinitis, comparing the treatment between desloratadine and intranasal budesonide.…”
Section: Discussionmentioning
confidence: 99%
“…These results in common cold have been backed up by other randomized double-blind studies of associated H1 antihistamines and pseudoephedrine in allergic rhinitis [17][18][19][20][21][22]. Grosclaude et al [17] found that the association of an H1 antihistamine (cetirizine 5 mg) and pseudoephedrine (120 mg) for 15 days did not improve nasal congestion more than pseudoephedrine (120 mg) alone but did improve other symptoms.…”
Section: Benefit Of Ephedrine and Pseudoephedrine As Nasal Decongestantsmentioning
confidence: 89%
“…In allergic rhinitis with moderate asthma, Nathan et al [21] found efficacy compared to placebo for 4 weeks' associated H1 antihistamine (cetirizine 5 mg) and pseudoephedrine (120 mg). And finally, Mucha et al [22] found 15 days' oral pseudoephedrine (240 mg) to be more effective against nasal congestion than an oral leukotriene receptor antagonist (montelukast 10 mg). [26] 1 Angina pectoris Manini et al [27] 1 Myocardial infarction Pederson et al [28] 1 Myocardial infarction Lopez Lois et al [29] 1 Myoclonia and trembling Roberge et al [30] 1 Psychosis and ataxia Sotullo C.A.…”
Section: Benefit Of Ephedrine and Pseudoephedrine As Nasal Decongestantsmentioning
confidence: 99%
“…There was no difference in the outcome measures of nasal peak inspiratory flow and diurnal and nocturnal rhinoconjunctivitis quality-of-life scores. 35 Not only was there no difference between these 2 drugs in 3 measures of effectiveness, pseudoephedrine was superior to montelukast in the symptoms of nasal congestion, and no difference was found between the 2 drugs in tolerability.…”
Section: Editorial Subjects-in This Issue and In Previous Issuesmentioning
confidence: 96%